Structure of genetic diversity in marginal populations of black poplar (Populus nigra L.). (August 2015) - Jiang, Dechun; Wu, Guili; Mao, Kangshan; Feng, Jianju
Abstract: It has been hypothesized that populations at the margins of the distributional range of a species show reduced genetic diversity and increased inter-population differentiation compared to central populations. Here, we test this hypothesis by examining the structure of genetic diversity in marginal populations of black poplar, Populus nigra L. (Salicaceae). This species occurs mainly in Europe but its range extends to central Asia. We collected 117 individuals from 10 populations at the edge of the distributional range of the species in central Asia to examine the structure of genetic diversity based on genetic polymorphisms at 20 microsatellite markers. As expected, the genetic diversity within these marginal populations is relatively low, with an average observed heterozygosity Ho of 0.337 and an average expected heterozygosity He of 0.466, compared to the genetic diversity of populations from central distributions. However, we recovered very low genetic differentiation between populations, with an average Fst of 0.0745, a value similar to those reported for central populations. AMOVA analyses confirmed this result, showing that only 9.2% of the total variation could be attributed to between-population variance ( P < 0.001). Our findings do not fully support hypotheses about the structure of genetic diversity in marginal populations formed from observations on other species. We suggest that a high rate of outcrossing and possible postglacial colonization at the edge of the distributional range of this long-lived poplar may explain the observed structure of the genetic diversity.